Three-Dimensional Aspects of the Lingual Papillae and Their Connective Tissue Cores in the Tongue of Rats: A Scanning Electron Microscope Study - Gabriela de Souza Reginato; Cristina de Sousa Bolina; Ii-sei Watanabe; Adriano Polican Ciena (The Scientific World Journal)
The aim of the present study was to describe the tridimensional morphological characteristics of the lingual papillae and their connective tissue cores (CTCs) in Sprague Dawley rats. Four types of papillae were reported on the dorsal surface. Filiform papillae were distributed on the tongue surface and after epithelial maceration a conic and multifilamentary shape of the CTCs was revealed. Fungiform papillae were reported on the rostral and middle regions covered by a squamous epithelium. After the removal of the epithelium, the shape of a volcano with the taste orifice at its top was noted. Foliate papillae were composed of five pairs of epithelial folds situated on the lateral-caudal margin of the tongue. After the removal of the epithelium, they were shown to be limited by thin laminar projections. The vallate papilla with an oval shape was present in the caudal region and delimited by an incomplete groove. The morphological characteristics of the lingual papillae of Sprague Dowley rats, three-dimensional SEM images, and the types of papillae on the dorsal surface were similar to those reported previously in other rodent mammals. The maceration technique revealed the details of extracellular matrix with varied shapes form of connective tissue cores.